Wit and Wisdom of the Italian Renaissance. - Speroni, Charles (University of California Press, 2022)
This is the first ample collection of facetiae, or witty tales, from the Italian Renaissance to be published in English. Witty and wise anecdotes had been known to the ancient Greeks and Romans in the form of apothegms, but not until the Renaissance did the true facetia acquire an independent life and popularity, and begin to spread rapidly throughout Italy and beyond the Alps. The publication of Poggio Bracciolini's Liberfacetiarum was largely responsible for.
Description based upon print version of record.
Keywords: Italian literature -- Translations into English.; Italian wit and humor -- Translations into English.; Renaissance -- Italy.; Maxims, Italian.; Italian literature -- Translations into English; Italian wit and humor -- Translations into English; Maxims, Italian; Renaissance -- Italy